The design of the Coconut Peeling and Splitting Machine using TRIZ Method - Yohanes Patrik Adventus Banda; Julius Mulyono; Hadi Santosa (Universitas Muhammadiyah Sidoarjo, 2022)
Copra is one of the most interesting materials, is a type of coconut which is dried using a heating process. Copra is commonly used as a part of material to produce cleanser, for the human body, such as soap and shampoo. There is a big opportunity for using copra, so we need to design an equipment for supporting copra production efficiently and faster. This research aim is to help the farmers, so they can meet market needs which are increasing day by day. Copra processing still uses traditional production methods. This study aims to design a coconut stripping and splitting device using the TRIZ method. Doing a simple experiment, resulting shorter processing of coconut peeling and breaking, showed an average time of 39.65 seconds for each piece of coconut.